An Investigation of the Shearing Forces Using Blanked Carbon Steel Sheets - Jasim, Ahmad Saad; Khleif, Ali Abbar (Al-Nahrain Journal for Engineering Sciences, 2019)
An important challenge confronted when using blanking to machine sheet metal is the treatment of the shearing force in demand for great strength and heavy stock. One of the methods used to decrease the force wanted is the increase of a punch shear angle. In this work, experiments were conducted to study the effect of shear angle for blank has a diameter (50 mm) on shear force of a low carbon steel sheet (AISI 1008). Low carbon steel is a very common material used in fabrication of sheet metal components, with thickness of (0.5 mm). Tools used in the blanking tests were one traditional flat end punch and four different bevel sheared rooftop punches, which rooftop punches were compared to. and it (0°, 5°, 10°, 15°, 20°) a punches diameter (49.95 mm) by clearance (0.025mm) for each side , with a blanking speed (500mm/min). A special blanking die set is designed and manufactured and was a blank cut by a hydraulic press whose capacity (20 ton). The results showed that the blanking forces of (AISI 1008) low carbon steel metal could be decreased radically with best bevel punch geometry. Using (10°) shear angle at the punch end, the cutting forces decreased up to (90%) compared to the ones of the traditional flat end tool